Alveolar macrophages are critical for broadly-reactive antibody-mediated protection against influenza A virus in mice. Issue 1 (December 2017) - He, Wenqian; Chen, Chi-Jene; Mullarkey, Caitlin; Hamilton, Jennifer; Wong, Christine; Leon, Paul; Uccellini, Melissa; Chromikova, Veronika; Henry, Carole; Hoffman, Kevin; Lim, Jean; Wilson, Patrick; et al.
Abstract The aim of candidate universal influenza vaccines is to provide broad protection against influenza A and B viruses. Studies have demonstrated that broadly reactive antibodies require Fc–Fc gamma receptor interactions for optimal protection; however, the innate effector cells responsible for mediating this protection remain largely unknown. Here, we examine the roles of alveolar macrophages, natural killer cells, and neutrophils in antibody-mediated protection. We demonstrate that alveolar macrophages play a dominant role in conferring protection provided by both broadly neutralizing and non-neutralizing antibodies in mice. Our data also reveal the potential mechanisms by which alveolar macrophages mediate protection in vivo, namely antibody-induced inflammation and antibody-dependent cellular phagocytosis. This study highlights the importance of innate effector cells in establishing a broad-spectrum antiviral state, as well as providing a better understanding of how multiple arms of the immune system cooperate to achieve an optimal antiviral response following influenza virus infection or immunization. Broadly reactive antibodies that recognize influenza A virus HA can be protective, but the mechanism is not completely understood. Here, He et al. show that the inflammatory response and phagocytosis mediated by the interaction between protective antibodies and macrophages are essential for protection.